2020
DOI: 10.1080/17550874.2020.1735553
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the conservation status of Restrepia (Orchidaceae) reveals the threatened status of the genus

Abstract: Introduction35 Restrepia is a small orchid genus comprising 61 species (WCSP 2018) belonging to the 36 Pleurothallidinae, the largest sub-tribe in the Orchidaceae. These species are found throughout 37 Central America and in Venezuela, Colombia, Ecuador, Peru and Bolivia in South America, 38 growing at elevations between 1000 -3000 m a.s.l. in areas of montane rain forest. These forests 39 were identified as deforestation 'hotspots' by Mittermeier et al. (1999). Habitat loss and orchid 40 population decline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Self‐incompatibility and myophily are regarded as biological synapomorphies within the Pleurothallidinae (Barbosa et al, 2009). Consequently, the genus Restrepia is also thought to be myophilous (Pridgeon and Stern, 1983; Luer, 1996a; Millner, 2013), but this has yet to be confirmed in the wild. The morphology of both R. aberrans and R. chocoënsis differ sufficiently (Luer, 1996a) from other species in the genus that they may comprise two monotypic subgenera, Echmeles and Pachymeles , respectively (Luer, 1996a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self‐incompatibility and myophily are regarded as biological synapomorphies within the Pleurothallidinae (Barbosa et al, 2009). Consequently, the genus Restrepia is also thought to be myophilous (Pridgeon and Stern, 1983; Luer, 1996a; Millner, 2013), but this has yet to be confirmed in the wild. The morphology of both R. aberrans and R. chocoënsis differ sufficiently (Luer, 1996a) from other species in the genus that they may comprise two monotypic subgenera, Echmeles and Pachymeles , respectively (Luer, 1996a).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of Restrepia species are narrow endemics, with poorly researched distributions represented by few herbarium records (Millner, 2013). Preliminary research (H. J. Millner, unpublished data) has shown that with the exceptions of R. trichoglossa (Romand‐Monnier, 2013) and R. contorta (Millner, 2013), all species in the genus should have a minimum global classification of threat as vulnerable, with species found as narrow endemics in threatened locations classified as critically endangered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orchidaceae is considered one of the largest families of vascular plants and is found in almost every ecosystem worldwide [10]. Although a great number of orchid species are found in Ecuador, their survival is endangered due to climate change but also because of anthropic disturbances [11] such as habitat loss due to deforestation, soil erosion, and Diversity 2022, 14, 478 2 of 10 illegal commerce [12]. Even though they produce several thousand seeds in one pod, they are small and lack a nutrient supply for germination [6].…”
Section: Introductionmentioning
confidence: 99%